2019
DOI: 10.7150/ijbs.30114
|View full text |Cite
|
Sign up to set email alerts
|

RRM2 is a potential prognostic biomarker with functional significance in glioma

Abstract: Glioma is one of the most common brain tumors, suggesting the importance of investigating the molecular mechanism of gliomas. We studied the roles of Ribonucleotide Reductase Regulatory Subunit M2 (RRM2) in glioma. Expressions of RRM2 are higher in glioma tissues evidenced by TCGA data, western blot and immunohistochemistry. RRM2 is negatively correlated with glioma patient's survival. RNA-seq showed that genes involved in apoptosis, proliferation, cell adhesion and negative regulation of signaling were up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Furthermore, we explored the functional target of miR-338-3p in glioma. RRM2 has been revealed as an oncogene that promotes glioma cell proliferation and migration [24]. Here we validated RRM2 as a functional The RRM2 abundances at mRNA (A) and protein (B) levels were measured in A172 and U251 cells transfected with pcDNA3.1, pcDNA3.1/ KCNQ1OT1, pcDNA3.1/KCNQ1OT1 and miR-NC or miR-338-3p by qRT-PCR and western blot analysis.…”
Section: Overexpression Of Kcnq1ot1 Up-regulates Rrm2 Expression By Dmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, we explored the functional target of miR-338-3p in glioma. RRM2 has been revealed as an oncogene that promotes glioma cell proliferation and migration [24]. Here we validated RRM2 as a functional The RRM2 abundances at mRNA (A) and protein (B) levels were measured in A172 and U251 cells transfected with pcDNA3.1, pcDNA3.1/ KCNQ1OT1, pcDNA3.1/KCNQ1OT1 and miR-NC or miR-338-3p by qRT-PCR and western blot analysis.…”
Section: Overexpression Of Kcnq1ot1 Up-regulates Rrm2 Expression By Dmentioning
confidence: 77%
“…including bladder cancer, melanoma and oral squamous cell carcinoma [17][18][19]. Moreover, previous research has suggested that dysregulation of miR-338-3p is involved in glioma malignancy [20][21][22], and that Ribonucleotide reductase M2 (RRM2) may contribute to development of glioma [23,24]. More importantly, predictions using starBase 2.0 indicate potential complementary sequences between miR-338-3p and KCNQ1OT1 or RRM2, however sequence interactions between these targets have not been validated previously.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr) Fmentioning
confidence: 99%
“…The dysregulated cell cycle has been identified in many types of cancer 29 . Ribonucleotide reductase is an enzyme involved in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Another example was RRM2 and BRIP1, which was significantly correlated with each other in expression ( Figure 6C, R = 0.93 and p-value < 0.001). RRM2 had been found to promote the progression of human GBM and was a potential prognostic biomarker in glioma (Li et al, 2018a;Sun et al, 2019). BRIP1 was found to be an independent signature, which was correlated with worse prognosis in glioma (de Sousa et al, 2017).…”
Section: Rna-binding Protein Regulatory Network During Glioma Progresmentioning
confidence: 93%